2018
DOI: 10.35790/ecl.6.1.2018.18682
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan antara Status Gizi dan Sistem Imun Seluler pada Subyek Penyakit Ginjal Kronik Stadium V Hemodialisis di Instalasi Tindakan Hemodialisis RSUP Prof. Dr. R. D. Kandou Manado

Abstract: Chronic kidney disease (CKD) is a pathophysiological process with a diverse etiology that causes progressive decrease of renal function and is generally ended with renal failure. Patients with CKD are given low-protein and low-water diets that can affect their nutritional status and immune system. This study was aimed to determine the relationship between nutritional status and cellular immune system in patients with stage V CKD that had hemodialysis perfomed on them at the Installation of Hemodialysis of Prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…This is supported by Nurmaliza's research in 2019 which showed that the majority of toddlers with good nutritional status have mothers with good nutritional knowledge (Nurmaliza, 2019). Children aged 5 years are vulnerable to infectious diseases because their immune systems are not yet developed perfectly (Unawekla, 2018). This can be overcome in various ways, including providing good nutrition for toddlers (Yendi, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by Nurmaliza's research in 2019 which showed that the majority of toddlers with good nutritional status have mothers with good nutritional knowledge (Nurmaliza, 2019). Children aged 5 years are vulnerable to infectious diseases because their immune systems are not yet developed perfectly (Unawekla, 2018). This can be overcome in various ways, including providing good nutrition for toddlers (Yendi, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The number of lymphocyte cells was obtained from the calculation of the number of lymphocyte cells in the blood smear of mice (Mus musculus). The normal value of lymphocyte cells in humans is around 20-50% [11].…”
Section: Provision Of Phytochemical Extract Of Curcuma Domesticamentioning
confidence: 99%
“…Ketika terjadi serangan, antigen pada tubuh biasanya akan mulai menstimulasi sistem kekebalan tubuh (Astari & Roziaty, 2020). Sistem imun memiliki fungsi untuk menghasilkan antibodi (Unawekla et al, 2018). Sistem imun pertahanan pada makhluk hidup ada 2 yaitu sistem pertahanan bawaan atau non-spesifik (innate immunity) dan sistem pertahanan spesifik (adaptive immunity) (Aripin, 2019).…”
Section: Tinjauan Pustakaunclassified